The Metaphors Developed by the Teachers towards School Managers - Demirtas, Zulfu (Ani Yayincilik, 2011)
Problem Statement: Metaphor is a powerful mental tool for understanding and explaining a highly abstract, complex or conceptual phenomenon. The essence of metaphor, which is widely used in daily life not only in language but also in thoughts and actions, is the understanding and experiencing of a certain thing in comparison with a different thing. Metaphors have positive and negative aspects. Being aware of the strong and weak aspects of the metaphors used is beneficial for the individual and organization. In schools, the metaphors developed by the teachers towards themselves, managers and the school are important for organizational functioning. Purpose of Study: The purpose of this study was to determine the perceptions of the teachers working in primary schools of the concept of manager though metaphors. Methods: This study was designed as a qualitative research project based on analyzing and understanding social phenomenon within the environment in which teachers are involved. Data was collected using a written interview form containing an instruction and one open-ended question. The population of the study was volunteers, consisting of the teachers working in the Elazig, Diyarbakir, Batman, Sanliurfa, Kahramanmaras and Gaziantep provinces of Turkey in the 2008-2009 academic year. Findings and Results: Two hundred two teachers volunteered to participate in the study, and from the interview forms submitted, 172 forms were accepted. These 172 participants developed 95 metaphors about school managers. These metaphors were grouped under seven main themes. Four of these main themes comprised a total of 53 metaphors developed by 111 teachers, which emphasized the positive attitude, behaviors and roles of the managers. The remaining three main themes contained 42 metaphors developed by 61 teachers, and these metaphors concentrated on the negative attitude, behavior and roles of the managers. Conclusions and Recommendations: It can be suggested that the school managers who develop secure relationships with the teachers play the role of school leaders. Where the leaders motivate others and have a broad vision about education, these can become effective schools. An effective leader exhibits strong leadership in education issues, clearly describes his expectations of the students and the teachers, and involves the teachers in decision-making about their classes.
Ö?retmelerin Kendi Müdürleri Hakkında Geliştirdikleri Metaforlar
Keywords: Teacher; manager; metaphor; manager's metaphors